2020
DOI: 10.1088/1742-6596/1697/1/012130
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering and low-frequency noise in epitaxial graphene chips

Abstract: Graphene is considered as a promising candidate for manufacturing of sensors due to its extreme sensitivity to molecule absorption. In this work, we show the connection between the electrical and optical properties of epitaxial graphene chips grown on 4H-SiC and intended for the production of protein-based sensors. Using of a complex of techniques, including Raman spectroscopy, atomic force microscopy, Kelvin probe microscopy, study of I-V characteristics and low-frequency noise, it is shown that the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Indeed, for the EG417-C5, Е5, Е7 chips showing different values of excess noise, there are regions with frequency dependencies SU ~1/f γ having different values of γ up to 1.4 with a maximum SU value at 1.22 Hz for the EG417-C5 chip as shown in Figure 3b. Earlier, we have observed that the dependence of SU ~1/fγ (γ > 1) in graphene films and the chips is consistent with the Raman spectra data that demonstrate an inhomogeneous distribution of compressive stresses in graphene [32]. Studying of graphene topography in these chips reveals cracks in graphene shown in Figure 4a-c, and d (EG417-Е7, -C5) and extended For the remaining 18% of chips, the spread of S U values was in the range of 6 × 10 −13 to 8 × 10 −11 V 2 /Hz (Figure 3a).…”
Section: Resultssupporting
confidence: 89%
“…Indeed, for the EG417-C5, Е5, Е7 chips showing different values of excess noise, there are regions with frequency dependencies SU ~1/f γ having different values of γ up to 1.4 with a maximum SU value at 1.22 Hz for the EG417-C5 chip as shown in Figure 3b. Earlier, we have observed that the dependence of SU ~1/fγ (γ > 1) in graphene films and the chips is consistent with the Raman spectra data that demonstrate an inhomogeneous distribution of compressive stresses in graphene [32]. Studying of graphene topography in these chips reveals cracks in graphene shown in Figure 4a-c, and d (EG417-Е7, -C5) and extended For the remaining 18% of chips, the spread of S U values was in the range of 6 × 10 −13 to 8 × 10 −11 V 2 /Hz (Figure 3a).…”
Section: Resultssupporting
confidence: 89%
“…Reproducibility issues relating to the structural and physicochemical properties of graphene resistances are discussed in [ 1 , 7 , 11 , 12 ]. The inhomogeneity of the properties of graphene films over the chip area has led to the need to use several duplicate resistors in one biosensor.…”
Section: Introductionmentioning
confidence: 99%
“…The inhomogeneity of the properties of graphene films over the chip area has led to the need to use several duplicate resistors in one biosensor. This makes it possible to neutralize the effect of inhomogeneity of resistance values on the results of virus detection by the biosensor [ 1 , 7 , 11 ]. These works show that the hook effect [ 13 ] related to a nonlinear dependence of detected signals versus analyte concentration may cause the lack of reproducibility of detection.…”
Section: Introductionmentioning
confidence: 99%